2018
DOI: 10.1007/s10616-018-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

On reprogramming of tumor cells metabolism: detection of glycogen in the cell lines of hepatocellular origin with various degrees of dedifferentiation

Abstract: The reprogramming of cancer cells includes shifts in glucose and glycogen metabolism. The aim of our work was to check the ability of forming glycogen grains in hepatocellular tumor cell lines of various dedifferentiation levels. We studied the monolayer culture established in vitro after explanting cells from rat ascites Zajdela hepatoma strain C (ZH-C) as a "parental" line and its five daughter clonal sublines: the holoclonal sublines 3H, 5F, 6H and the meroclonal ones 1E, 9C, which possess, respectively, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…This observation lends further support to the presumption that the malignant potential of HCC correlates with increasing metabolic distance from the normal hepatocyte. It has to be noted, however, that studies with different tumor cell lines of hepatocellular origin did not show distinct correlation between the degree of tumor cell dedifferentiation and their ability to accumulate glycogen [40]. A high glycolytic capacity and the ability to store large amount of glycogen are often viewed as adaptation to hypoxic conditions, but the correlation between glucose uptake rates and glycogen content was insignificant (R 2 = 0.073) in our study.…”
Section: Carbohydrate Metabolismcontrasting
confidence: 86%
“…This observation lends further support to the presumption that the malignant potential of HCC correlates with increasing metabolic distance from the normal hepatocyte. It has to be noted, however, that studies with different tumor cell lines of hepatocellular origin did not show distinct correlation between the degree of tumor cell dedifferentiation and their ability to accumulate glycogen [40]. A high glycolytic capacity and the ability to store large amount of glycogen are often viewed as adaptation to hypoxic conditions, but the correlation between glucose uptake rates and glycogen content was insignificant (R 2 = 0.073) in our study.…”
Section: Carbohydrate Metabolismcontrasting
confidence: 86%
“…Moreover, ChIP-seq analysis of mouse liver tissue predicted ChREBP DNA binding at loci corresponding to glycogen synthase ( Gys2 ) and glycogen phosphorylase ( Pygl ) [ 13 ], genes encoding hepatic enzymes that mediate glycogen synthesis and breakdown, hence consuming and producing hepatic G6P, respectively. Hepatic glycogen accumulation is emerging as a contributor to hepatopathy and liver tumor formation [ [14] , [15] , [16] , [17] , [18] ], while ChREBP has been proposed to play a pro-oncogenic role in the liver [ 16 , 19 , 20 ]. We previously reported that normalizing hepatic ChREBP activity, increased hepatic glycogen content and lowered blood glucose levels in hepatocyte-specific glucose-6-phosphatase ( G6pc ) knockout mice, a model for hepatic GSD type Ia [ 9 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%